Developments for future EU7 regulations and the path to zero impact emissions – A catalyst substrate and filter supplier's perspective - Thorsten Boger; Dominik Rose; Suhao He; Ameya Joshi (Transportation Engineering, 2022)
New EU7 emission standards are currently under development. While the timing and exact level of stringency of these standards is not available, both OEMs and suppliers are preparing to meet significantly reduced tailpipe NOx and particle number standards for both light- and heavy-duty vehicles. We present here some of the emission control systems that are likely to be implemented and details on the advanced component technologies.